2021
DOI: 10.3390/agronomy11071311
|View full text |Cite
|
Sign up to set email alerts
|

Productive Characteristics and Fruit Quality Traits of Cherry Tomato Hybrids as Modulated by Grafting on Different Solanum spp. Rootstocks under Ralstonia solanacearum Infested Greenhouse Soil

Abstract: Grafting is increasingly becoming an indispensable tool that minimizes the risks associated with intensive vegetable production systems, including soil-borne diseases. This study assesses the performance of two cherry tomato hybrids (‘Cheramy’ and ‘Sheeja’) grafted onto three tomato and five eggplant local rootstock genotypes (cultivated/wild) under Ralstonia solanacearum (bacterial wilt)-infested greenhouse soil. The impact of grafting on growth, yield and fruit physical quality was mainly influenced by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 74 publications
(95 reference statements)
0
12
0
Order By: Relevance
“…Tomato is one of the most important vegetable crop in Egypt and it’s grown all year round in Egypt. However, production faces some problems in summer season due to high temperature and insect born viruses diseases prevailing in this time period [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tomato is one of the most important vegetable crop in Egypt and it’s grown all year round in Egypt. However, production faces some problems in summer season due to high temperature and insect born viruses diseases prevailing in this time period [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between scion and rootstock will increase the xylem microtubule system to promote growth and affect rootstock’s water movement and photosynthesis process, while scion mainly affects the fruit’s physical and chemical quality characteristics of fruit ( Zaaroor-Presman et al., 2020 ; Reyes-Herrera et al., 2020 ; Naik et al., 2021 ; Cañas-Gutiérrez et al., 2022 ). The scion of variety affects the growth and development of rootstock through various stimulation signals.…”
Section: Discussionmentioning
confidence: 99%
“…lycopersicum ) fruit dry matter content, total sugars, and TA varied with rootstock‐scion combinations. Naik et al 13 . demonstrated that under bacterial‐wilt‐infested greenhouse conditions, the SSC and TA of cherry tomatoes were also affected by rootstock‐scion combinations.…”
Section: Introductionmentioning
confidence: 99%
“…lycopersicum) fruit dry matter content, total sugars, and TA varied with rootstock-scion combinations. Naik et al 13 demonstrated that under bacterial-wilt-infested greenhouse conditions, the SSC and TA of cherry tomatoes were also affected by rootstock-scion combinations. Mauro et al 14 did a comprehensive study, grafting cherry tomatoes of distinct sizes with eight rootstocks from four genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%